Un caso de Tinea unguium producido por Microsporum gypseum (Bodin, 1907) Guiart et Grigorakis, 1928 - Ruiz, Armando (Revista de Biología Tropical, 1953)
The author describes a case of onychomycosis by Microsporum gypseum (Bodin, 1907) Guiart et Grigorakis, 1928. The case is of interest since the species of the genus Microporum have raraley been found causing Tinea unguium.